M88. Regional Cortical Folding and Thickness Differences Between Schizophrenia Patients With and Without a History of Severe Violence - Storvestre, Guttorm (Schizophr Bull, 2017)
Background: Clinical studies in schizophrenia patients (SCZ) with a history of violence are practically and ethically challenging, hence the neurobiological underpinnings of violence in SCZ are largely unknown. Searching for cortical markers of violent SCZ, this is to the best of our knowledge the first complete cortical morphology (ie, folding, thickness, and area) study in violent SCZ. Methods: Structural 3T MRI scans were acquired of 47 subjects (violent SCZ n = 11, mean age 33.2 years (SD 9.0), 91% male; SCZ n = 17, 34.3 years (7.4), 94% male; HC n = 19, 33.2 years (SD 9.1), 90% male). Violent offences included murder, attempted murder, or severe assault towards other people. DSM-IV diagnoses of schizophrenia were SCID-I verified Regional cortical volume, thickness, area, and folding (lGI) estimates were obtained with the FreeSurfer 5.3.0 software. We used smoothing of 10 mm for the analysis of volume, area and thickness and none for the lGI analyses. Diagnostic group differences were analyzed by the use of GLMs co-varying for age, and exploratory across the entire cortical mantle. Nonparametric clusterwise correction for multiple comparisons was performed with the Monte Carlo simulation tool in FreeSurfer. The initial cluster forming threshold was set to P < .5 and clusters with an empirical P < .5 were considered significant. Results: Violent SCZ patients had increased cortical folding in the visual (lateral occipital) cortex bilaterally and left lateral orbitofrontal cortex compared to nonviolent SCZ patients. Compared to HC, violent SCZ folding patterns differed in the lateral orbitofrontal-, inferior temporal-, inferior parietal-, supramarginal-, postcentral-, lingual-, and pericalcarine cortex. Violent SCZ patients had reduced cortical thickness in the left precentral-, inferior parietal-, superior temporal- and the right fusiform cortex compared to nonviolent SCZ patients, and reduced thickness in the left fusiform- and right inferior parietal-, superior frontal-, and lingual cortex compared to HC. There were no group differences in cortical volume or area. Conclusion: Violent SCZ patients show regionally reduced cortical thickness and increased folding compared to nonviolent SCZ patients. Differences were found in cortical areas involved in visual and auditive processing, face and emotion recognition, and emotion and reward in decision-making. While the timing and origin of the cortical thickness reduction could reflect several genetic, disease-related or environmental factors, the cortical folding abnormalities suggests that aberrant neurodevelopment is of importance to violence in SCZ. Future studies are needed to explore the functional consequences of the observed differences.